Influence of surface characteristics on the penetration rate of electrolytes into model cells for lithium ion batteries. Issue 8 (17th April 2020) - Beyer, Sebastian; Kobsch, Oliver; Pospiech, Doris; Simon, Frank; Peter, Christian; Nikolowski, Kristian; Wolter, Mareike; Voit, Brigitte
Abstract: Filling of cells with liquid electrolytes is the time-determining step in the production of lithium-ion batteries (LIBs). The influencing factors are not completely understood and need further research. The adhesion of the solid components, i.e. anode, cathode and separators, to the electrolyte and the respective interfaces play an important role. In this study, the penetration of liquid electrolytes is monitored by a combination of tensiometry and chronoamperometry. A setup including all battery components is proposed as model for battery cells. Diethyl carbonate is employed as model for the electrolyte. The penetration rates of the liquid into a stepwise extended model setup (separator; anode; cathode; separator/anode; separator/cathode; and anode/separator/cathode) in confined geometry between glass plates are determined with reproducible results. A modified Washburn equation combining surface tensions of liquid and solids forming the interface, and complex geometries of separators and electrodes is used to develop the penetration model. Comparative measurements in a glove box yield comparable results with the real electrolyte solution. The penetration of the model electrolyte into ceramic-coated separators is significantly faster than into polyolefin separators due to higher surface roughness and higher polarity of ceramic-coated separators. The wetting times obtained by chronoamperometric measurements correlate with the tensiometric penetration rates. The higher the tensiometric penetration rate, the lower is the chronoamperometric wetting time. The results of the study contribute to a deeper understanding of the interactions between electrolyte and solid components in LIBs and provide a new method to pre-evaluate battery components.